2021
DOI: 10.1038/s41467-021-26621-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear S-nitrosylation impacts tissue regeneration in zebrafish

Abstract: Despite the importance of nitric oxide signaling in multiple biological processes, its role in tissue regeneration remains largely unexplored. Here, we provide evidence that inducible nitric oxide synthase (iNos) translocates to the nucleus during zebrafish tailfin regeneration and is associated with alterations in the nuclear S-nitrosylated proteome. iNos inhibitors or nitric oxide scavengers reduce protein S-nitrosylation and impair tailfin regeneration. Liquid chromatography/tandem mass spectrometry reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…And while both ROS and RNS have been shown to play roles during cell proliferation and new tissue growth, the mechanisms of RNS signaling during regeneration are much less well understood [85,86]. Although a recent study has demonstrated a role for NO during zebrafish fin regeneration [87], the role of RNS in the regenerative process is still largely uncharacterized and its role during planarian regeneration is currently unknown. Given the potential, based on the radical pair mechanism, for WMF interactions with RNS signaling during tissue growth, this is a promising area for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…And while both ROS and RNS have been shown to play roles during cell proliferation and new tissue growth, the mechanisms of RNS signaling during regeneration are much less well understood [85,86]. Although a recent study has demonstrated a role for NO during zebrafish fin regeneration [87], the role of RNS in the regenerative process is still largely uncharacterized and its role during planarian regeneration is currently unknown. Given the potential, based on the radical pair mechanism, for WMF interactions with RNS signaling during tissue growth, this is a promising area for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In similar experimental settings, we next detected the transcript level expression of NO-responsive genes in EC using qPCR experiment. Based on previously reported data sets, we choose to detect the transcript level of NO responsive genes; VEGFa, TBX20, MMP2, FGF2, KDR, TIE2, TEK, and Angiopoietin-2 26 . Through this analysis, we detected significant increase in expression of VEGFa, TBX20, MMP2, FGF2, and Angiopoietin-2 upon NO exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They also demonstrated that NO signaling results in increased protein S-nitrosylation. This later process may however be beneficial as Matrone et al demonstrated that inhibition of the NO synthase iNOS results in reduced nuclear S-nitrosylation and impaired regeneration following tail fin amputation [306].…”
Section: Induction Of Inflammationmentioning
confidence: 99%